2008
DOI: 10.1063/1.2839381
|View full text |Cite
|
Sign up to set email alerts
|

Optical spin manipulation of electrically pumped vertical-cavity surface-emitting lasers

Abstract: We analyze the potential for the spin manipulation of vertical-cavity surface-emitting lasers (VCSELs) by operating them electrically and injecting additional spin-polarized carriers by polarized optical excitation. The output polarization of the VCSELs can be easily controlled by the spin orientation of the optically injected carriers when the injection current does not exceed the threshold current

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(56 citation statements)
references
References 19 publications
2
54
0
Order By: Relevance
“…Which material and device properties lead to either chaos polarization switching or stochastic polarization switching is a challenging question in the development of polarizationcontrolled microcavity lasers. Since the underlying physics is a nonlinear carrier spin coupling, one could take advantage of and make a connection with recent works on spin control by carrier injection 45 or variation of the quantum well composition 46 . Secondly, the polarization chaos reported here has frequencies that are not limited by the laser relaxation oscillations, as suggested by the SFM model and as can be expected from the recent works on spin-controlled VCSEL 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Which material and device properties lead to either chaos polarization switching or stochastic polarization switching is a challenging question in the development of polarizationcontrolled microcavity lasers. Since the underlying physics is a nonlinear carrier spin coupling, one could take advantage of and make a connection with recent works on spin control by carrier injection 45 or variation of the quantum well composition 46 . Secondly, the polarization chaos reported here has frequencies that are not limited by the laser relaxation oscillations, as suggested by the SFM model and as can be expected from the recent works on spin-controlled VCSEL 47 .…”
Section: Discussionmentioning
confidence: 99%
“…7(c) and 7(d). For this case, the emitted light S − exceeds that with the opposite helicity, S + , there is a gain asymmetry, 5,6,8 another consequence of the polarizationdependent gain. The zero gain is attained at µ C+ − µ V for spin up (red curves) and µ C− − µ V for spin down transitions (blue curves).…”
Section: Understanding the Spin-dependent Gainmentioning
confidence: 99%
“…It was experimentally demonstrated that injecting spinpolarized carriers already leads to noticeable differences in the steady-state operation. [4][5][6] The onset of lasing is attained for a smaller injection, lasing threshold reduction, while the optical gain differs for different polarizations of light, leading to gain asymmetry, also referred to as gain anisotropy. 5,6,8 In the stimulated emission, even a small carrier polarization in the active region can be greatly amplified and lead to the emission of completely circularly polarized emitted light, an example of a very efficient spin filtering.…”
Section: Introductionmentioning
confidence: 99%
“…As a specific example of spintronic devices, spin-polarized vertical-cavity surface-emitting lasers (VCSELs) have attracted considerable attention [5][6][7][8][9]. In such lasers, the output polarization is controlled by injecting spin-polarized electrons into the laser active region.…”
Section: Introductionmentioning
confidence: 99%